Sex-related differences in long-term mortality after coronary artery bypass graft surgery: a systematic review and meta-analysis. (14th October 2021) - Al-Sadawi, M; Kane, J; Stevens, G A; Parikh, P
Abstract: Background: This meta-analysis assessed the sex-related differences in long-term mortality (>7 years) after Coronary Artery Bypass Graft (CABG) Surgery. Purpose: Women has higher incidence of short-term cardiovascular mortality after CABG compared to men. However, data about long-term differences are controversial. Methods: We searched the databases for studies reporting sex-specific mortality following CABG including Ovid MEDLINE, Ovid, Embase, Scopus, Web of Science, Google Scholar, and EBSCO CINAHL from inception up to December 31st, 2020. The search was not restricted to time or publication status. Outcomes included rates of long-term mortality (>7 year or longer). Results: A total of 518 studies were resulted from literature search. A total of 14 studies and 204, 223 patients; 158, 663 men and 45, 556 women, with a mean age of the men 60.2 years and 63.2 years for women, were included in our systematic review and meta-analysis. Our analysis suggested sex-related differences in long-term mortality (>7 years) following CABG (odds ratio (1), 1.15; 95% confidence interval (2), 1.017–1.30; P<.02). Conclusions: Our results suggest that women had higher long-term mortality following CABG compared with men. It is the largest study to date of sex-specific differences in long-term mortality (>7 years). FUNDunding Acknowledgement: Type of funding sources: None.